Self‐Healable Spider Dragline Silk Materials - Chen, Wen‐Chia; Wang, Ruei‐Ci; Yu, Sheng‐Kai; Chen, Jheng‐Liang; Kao, Yu‐Han; Wang, Tzi‐Yuan; Chang, Po‐Ya; Sheu, Hwo‐Shuenn; Chen, Ssu‐Ching; Liu, Wei‐Ren; Yang, Ta‐I; Wu, Hsuan‐Chen (Advanced functional materials, 2023)
Developing materials with structural flexibility that permits self‐repair in response to external disturbances remains challenging. Spider silk, which combines an exceptional blend of strength and pliability in nature, serves as an ideal dynamic model for adaptive performance design. In this work, a novel self‐healing material is generated using spider silk. Dragline silk from spider Nephila pilipes is demonstrated with extraordinary in situ self‐repair property through a constructed thin film format, surpassing that of two other silks from spider Cyrtophora moluccensis and silkworm Bombyx mori . Subsequently, R2, a key spidroin associated with self‐healing, is biosynthesized, with validated cohesiveness. R2 is further programmed with tunable healability (permanent and reversible) and conductivity (graphene doping; R2G) for electronics applications. In the first demonstration, film strips from R2 and R2G are woven manually into multidimensional (1D‐3D) conductive fabrics for creating repairable logic gate circuits. In the second example, a reversibly‐healable R2/R2G strip is fabricated as a re‐configurable wearable ring probe to fit fingertips of varying widths while retaining its detecting capabilities. Such a prototype displays a unique conformable wearable technology. Last, the remarkable finding of self‐healing in spider silk can offer a new material paradigm for developing future adaptive biomaterials with tailored performance and environmental sustainability.